2000
DOI: 10.1021/ac991031j
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sensing on a DNA Probe-Modified Electrode Using Ferrocenylnaphthalene Diimide as the Electrochemically Active Ligand

Abstract: Naphthalene diimide derivative 1 carrying ferrocenyl moieties at the termini of imide substituents binds intact calf thymus DNA 4 times more strongly than the denatured DNA, and its complex with the intact DNA dissociates 80 times more slowly than that with the denatured DNA. On the basis of these observations, ligand 1 was applied to a probe of electrochemical DNA sensing. A thiol-linked single-stranded DNA probe was immobilized through the S-Au bonding to 20-30 pmol/mm2 on a gold electrode. Following hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
221
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(228 citation statements)
references
References 25 publications
(29 reference statements)
5
221
1
1
Order By: Relevance
“…Hashimoto et al, proposed the immobilisation of a synthetic 20-mer dsDNA and the subsequent regeneration of a free DNA probe by duplex alkaline denaturation (Hashimoto et al, 1998). The immobilisation of a 20-mer probe, with the subsequent masking of the unmodified gold regions with mercaptoethanol spacers, has been reported (Takenaka et al, 2000;Kertesz et al, 2000). A mixed monolayer of 10-mer cysteine-conjugated PNA probe and 6-mercapto-1-hexanol was used by Umezawa and co-workers to modified gold disk electrodes (Aoki et al, 2000).…”
Section: Direct Self-assembly Of Alkanethiol-functionalised Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hashimoto et al, proposed the immobilisation of a synthetic 20-mer dsDNA and the subsequent regeneration of a free DNA probe by duplex alkaline denaturation (Hashimoto et al, 1998). The immobilisation of a 20-mer probe, with the subsequent masking of the unmodified gold regions with mercaptoethanol spacers, has been reported (Takenaka et al, 2000;Kertesz et al, 2000). A mixed monolayer of 10-mer cysteine-conjugated PNA probe and 6-mercapto-1-hexanol was used by Umezawa and co-workers to modified gold disk electrodes (Aoki et al, 2000).…”
Section: Direct Self-assembly Of Alkanethiol-functionalised Probesmentioning
confidence: 99%
“…The shielding of the ferro-ferri-cyanide ions from the DNA-modified surface was attributed to a combination of physical coverage by the ssDNA and the electrostatic repulsion between the negatively charged redox couple ions and the DNA phosphate backbone (Yang et al, 1998). Takenaka et al (2000) reported an indirect quantification method based on the HPLC analysis of the excess of DNA remained unadsorbed.…”
Section: Direct Self-assembly Of Alkanethiol-functionalised Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…56,58,59 DNA-based electrochemical methods have also been developed primarily to detect nucleic acid hybridization. 44,45,[60][61][62][63][64][65][66][67][68][69][70][71][72][73] Notably, those methods do not rely on an intercalator as the redox probe. General principles governing electron transport through modified films involving percolation or the physical displacement of associated ions are also well understood.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques employ species exhibiting i) well-pronounced electrochemistry at less extreme potentials, involving reversible or catalytic electrode processes, and/or ii) non-covalent or covalent structure-selective interactions with DNA. Electroactive non-covalent binders including DNA intercalators (metal chelates such as [Co(phen) 3 ] 3 [11], daunomycin [12], a bis-intercalator bis-9-acridinyl derivative with a viologen linker [13] or a threading intercalator ferrocenyl-coupled naphthalene diimide [14]) or groove binders (Hoechst 33258 [15]) selectively recognizing duplex DNA have been used as redox indicators of DNA hybridization at the electrode surface. Other authors used covalent labeling of target DNA or hybridization (reporter) probes with electroactive markers (such as ferrocene derivatives [16]) or enzymes taking part in electrocatalytic processes (peroxidase [17]).…”
Section: Introductionmentioning
confidence: 99%